2015
DOI: 10.1016/j.bbamcr.2015.09.028
|View full text |Cite|
|
Sign up to set email alerts
|

Tensin1 positively regulates RhoA activity through its interaction with DLC1

Abstract: DLC1 is a RhoGAP-containing tumor suppressor and many of DLC1’s functions are absolutely dependent on its RhoGAP activity. Through its RhoGAP domain, DLC1 inhibits the activity of RhoA GTPase, which regulates actin cytoskeleton networks and dis/assembly of focal adhesions. Tensin1 (TNS1) is a focal adhesion molecule that links the actin cytoskeleton to integrins and forms signaling complexes through its multiple binding domains. Here, we report that TNS1 enhances RhoA activity in a DLC1-dependent manner. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 24 publications
2
56
1
Order By: Relevance
“…Similarly, DLC1 localizes to focal adhesions through its interaction with tensin proteins, which link the actin cytoskeleton to integrins [108][109][110] . Tensins sequester DLC1 away from RhoA, thereby increasing RhoA activity.…”
Section: Ring Domainmentioning
confidence: 98%
“…Similarly, DLC1 localizes to focal adhesions through its interaction with tensin proteins, which link the actin cytoskeleton to integrins [108][109][110] . Tensins sequester DLC1 away from RhoA, thereby increasing RhoA activity.…”
Section: Ring Domainmentioning
confidence: 98%
“…Nevertheless, only full-length tensin 3 could stimulate Dock5 activity, suggesting that, as in the case of Dlc1 (Shih et al, 2015), the functional interaction between tensin 3 and Dock5 is complicated. The activation of Dock5 by tensin 3 might involve conformational cues provided by full-length tensin 3 as well as other partners of the protein, which would need more extensive investigation.…”
Section: Manzanaresmentioning
confidence: 99%
“…At the molecular level, the function of tensins is also a matter of debate. The SH2-PTB domain of tensins can bind and inhibit Dlc-family RhoGAPs (Shih et al, 2015) whereas, the ABD of tensin 3 has been shown to stimulate the RhoGAP activity by relieving Dlc1 intramolecular inhibition mediated by its N-terminal SAM domain (Cao et al, 2012). Upon EGF or PDGF stimulation, tensin 3 can also associate with phosphoinositide 3-kinase (PI3K) and promote Rac activation at the leading edge of the cell (Cao et al, 2015).…”
Section: Manzanaresmentioning
confidence: 99%
See 1 more Smart Citation
“…DLC1 negatively regulates RhoA GTPase activity through its RhoGAP domain, which is essential for DLC1's tumor suppression function [12, 14]. Its RhoGAP activity is tightly regulated through phosphorylation by CDK5 [20] or ERK [15] as well as binding partners such as tensins [3, 18], which also recruit DLC1 to focal adhesions. On the other hand, not all suppression roles rely on controlling RhoA function.…”
Section: Introductionmentioning
confidence: 99%